ANALISIS PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KOMITMEN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT.PANCA BUANA PLASINDO MEDAN - Irwadi Bangun (Jurnal Manajemen Akuntansi Dan Administrasi Bisnis, 2020)
This study aims to describe the influence of transformational leadership, work commitment and compensation on employee performance at PT. PancaBuanaPlasindo Medan. This research was conducted at PT. PancaBuanaPlasindoMedan which last for 3 (three) months, starting from June 2019 until august 2019. This researsh use stratified random sampling method. Reseaarsh respondents are all employees hose machine of PT. PancaBuanaPlasindo Medan which is 65 (sixtyfive) people. The instrument usesisa questionnaire to colect data on transformational leadership variables, work commitment variables, compensation variables and employees performance variables. Data analysis tecnique used is validity test, reliability test, descriptive analysis, multicollinearity test, normality test, multiple linear regression analysis, multiple linear correlation coefficient test, partial hypothesis test or t test, simultanneous hypothesis test or F test, and calculation of coeffisient of determination. The result of descriptive analysis for transformational leadership variable,work commitment variables, compensation variables is in good category and employees performance variables is in enough category at PT. PancaBuanaPlasindo Medan. Best on partial analysis, transformational leadership, commitment and compensation have a positive and significant influence on employee performance at PT PancaBuanaPlasindo Medan; Simultaneously, transformational leadership, work commitment and compensation have a positive and significant impact on employee performance at PT. PancaBuanaPlasindo Medan. Contribution of transformational leadership variabel, work commitment variables, compensation variables to improve employees performance variables at PT. PancaBuanaPlasindo Medan is equal to 0,732 or 73,2%, while the remaining 0,268 or 26,8% is influenced by other variables not examined by the authors in this study, such as comunication, work environment, work motivation, job satisfication and other etc.